Catalyst as well as preparation method and application thereof

By loading PtO nanoclusters on the Mo2C support and controlling the reaction conditions, the problems of low load utilization, poor dispersion and poor stability of the existing Pt-based catalysts are solved, and a catalyst with high activity and stability is achieved, which is suitable for hydrogen production by electrolyzing water.

CN119571365AActive Publication Date: 2025-03-07WUHAN UNIV OF SCI & TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411954238.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-07
Estimated Expiration
2044-12-27

AI Technical Summary

Technical Problem

The existing precious metal Pt-based composite catalysts have problems such as low load utilization, poor dispersion, poor stability and difficult synthesis.

Method used

The nanostructured Mo2C is used as a carrier and loads PtO nanoclusters. PtO is accurately synthesized by controlling the flow rate of atmosphere during the reaction, and the nanostructure of Mo2C is used to improve the stability and activity of PtO.

Benefits of technology

The high activity and stability of PtO catalysts are achieved, the kinetics of hydrogen evolution reactions are improved, the cost of catalysts is reduced, and the excellent electrocatalytic performance is shown in the field of electrolytic hydrogen production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005215511250000011
    Figure HDA0005215511250000011
  • Figure HDA0005215511250000012
    Figure HDA0005215511250000012
  • Figure HDA0005215511250000021
    Figure HDA0005215511250000021
Patent Text Reader

Abstract

The invention discloses a catalyst as well as a preparation method and application thereof. The catalyst comprises a Mo2C carrier with a nano structure and a PtO nanocluster loaded on the Mo2C carrier. The method comprises the following steps: mixing a Mo2C carrier with a nanostructure with a platinum-containing metal compound solution to obtain a mixed solution; carrying out stirring reaction on the mixed solution at 50-95 DEG C for 0.5-5 hours, and continuously introducing a reaction atmosphere; and after the reaction is finished, filtering, washing and drying to obtain the catalyst. According to the preparation method, synthesis of PtO can be accurately controlled, meanwhile, sufficient anchoring points are provided for the PtO nanocluster by utilizing the large specific surface area and rich surface dangling bonds of the Mo2C nanostructure, the uniformity, dispersity and stability of loading of the PtO nanocluster on the surface of the Mo2C material are greatly improved, good electro-catalysis hydrogen evolution performance is shown, and the preparation method is suitable for industrial production. The effective load rate of Pt is greatly improved, the use amount of Pt is reduced, and the cost of the catalyst is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrocatalysis, and in particular relates to a catalyst and a preparation method and application thereof. Background Art

[0002] With the consumption of fossil energy, hydrogen energy has attracted widespread attention due to its high energy density, abundant reserves, and clean and pollution-free properties. The electrolysis of water to produce hydrogen is considered to be very promising. Current studies have shown that platinum (Pt)-based catalysts have the best hydrogen evolution performance under acidic conditions. However, the alkaline hydrogen evolution activity of metal Pt catalysts is obviously insufficient and the electrochemical stability is poor. At the same time, the price of Pt materials is expensive. Therefore, it is of great significance to study and develop Pt-based catalysts with low loading and high activity under full pH conditions. Dispersing Pt on a carrier can effectively reduce the loading amount and size of Pt and effectively improve the electrochemical activity of Pt. Carbon is the most widely used carrier material in industry. The Pt loading of commercial platinum-carbon (Pt / C) catalysts is mostly 20wt% and 40wt%, but it is expensive, has few exposed reaction active sites, and has problems such as unstable catalyst interface and short service life. At the same time, some oxidation products of carbon carriers, such as carbon monoxide, will be strongly adsorbed on the Pt surface, further reducing the catalytic activity of Pt. Therefore, further exploring different carrier materials and optimizing precious metal Pt-based materials and their preparation processes are of great research and application significance. Summary of the invention

[0003] The main purpose of the present invention is to provide a catalyst and a preparation method and application thereof in view of the problems and shortcomings of the prior art, which can solve the problems of low load utilization, poor dispersion, poor stability and difficult synthesis of the existing precious metal Pt-based composite catalysts.

[0004] In order to solve the above technical problems, the technical solution of the present invention is as follows:

[0005] A catalyst comprises a nanostructured Mo2C carrier and PtO nanoclusters supported on the Mo2C carrier.

[0006] In the above scheme, the size of the PtO nanoclusters is 2-5 nm.

[0007] In the above scheme, the Pt loading is 0.1-10wt%.

[0008] In the above scheme, the nanostructure morphology of the Mo2C is flake-shaped, flower-shaped, ribbon-shaped, tubular or linear.

[0009] The method for preparing the catalyst comprises the following steps:

[0010] The nanostructured Mo2C support is mixed with a platinum-containing metal compound solution to obtain a mixed solution;

[0011] The mixed solution was stirred and reacted at 50°C-95°C for 0.5h-5h, and the reaction atmosphere was continuously introduced;

[0012] After the reaction is completed, the catalyst is obtained after filtering, washing and drying.

[0013] In the above scheme, the platinum-containing metal compound includes a combination of one or more of ammonium hexachloroplatinate, chloroplatinic acid hexahydrate or platinum dichloride.

[0014] In the above scheme, the concentration of the platinum metal compound solution is 0.2-0.4 mM / L.

[0015] In the above scheme, the mass ratio of the Pt element content in the mixed solution to Mo2C is 1-10:100.

[0016] In the above scheme, the reaction atmosphere is oxygen or an oxygen-containing atmosphere.

[0017] In the above scheme, the flow rate of the reaction atmosphere is 140-200 sccm.

[0018] In the above scheme, the platinum metal compound solution is an aqueous solution or an alcohol solution.

[0019] The catalyst is used in electrocatalytic hydrogen production.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] 1) The method of controlling the flow rate of the atmosphere introduced during the reaction process is used to accurately control the synthesis of the intermediate transition state PtO of the Pt metal oxide. The catalytic performance of PtO is better than that of metal Pt because the long Pt-O bond is conducive to proton-electron coupling and accelerates the release of H2. However, PtO belongs to the transition state of metal Pt oxidation, has poor stability, and is easily oxidized to a highly oxidized state of PtO2 during the synthesis process. Therefore, the present invention can accurately control the synthesis of PtO, while utilizing the carrier effect to improve the stability of PtO and improve the activity of the PtO catalyst under alkaline conditions.

[0022] 2) Nano-Mo2C is used as a carrier of PtO. The Pt loading in the Mo2C-PtO material can be controlled by adjusting the feed ratio of different platinum-containing metal compounds to Mo2C. The large specific surface area and abundant dangling bonds on the surface of the Mo2C nanostructure are used to provide sufficient anchoring points for PtO nanoclusters, which greatly improves the uniformity, dispersibility and stability of the PtO nanoclusters loaded on the surface of the Mo2C material, greatly improves the effective loading rate of Pt, reduces the amount of Pt used, and reduces the catalyst cost.

[0023] 3) The extremely small PtO nanoclusters prepared by this method are dotted on the surface of the highly conductive Mo2C matrix, which greatly promotes the electronic interaction between the interfaces, enhances the activation ability of interfacial water, and greatly improves the kinetics of hydrogen evolution reaction. At the same time, the Mo2C matrix itself also acts as a hydrogen evolution active phase, increasing the density of active sites, thereby showing good electrocatalytic hydrogen evolution performance, which is better than most platinum-based electrocatalysts and has a very broad application prospect in the field of hydrogen production by electrolysis of water;

[0024] 4) The preparation method of the present invention is simple, uses no other raw materials except the platinum source, has no by-products, has a high product purity, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 Schematic diagram of the preparation process of the Mo2C-PtO material of the present invention;

[0026] Figure 2 The XRD patterns of the Mo2C-PtO materials prepared in Examples 1 to 3 of the present invention;

[0027] Figure 3 The XPS spectra of the Mo2C-PtO materials prepared in Examples 4 and 5 of the present invention;

[0028] Figure 4 This is a scanning electron microscope image of the Mo2C-PtO material prepared in Example 1 of the present invention;

[0029] Figure 5 This is a transmission electron microscope image of the Mo2C-PtO material prepared in Example 1 of the present invention;

[0030] Figure 6 This is the element distribution diagram of the Mo2C-PtO material prepared in Example 1 of the present invention, wherein Figure 6 a is the dark field image of transmission electron microscope, Figure 6 b, c, e, and f are the distribution diagrams of Pt, C, Mo, and O elements, respectively. Figure 6 d is the summary diagram of all element distribution;

[0031] Figure 7 This is a scanning electron microscope image of the Mo2C-PtO material prepared in Example 2 of the present invention;

[0032] Figure 8 This is a transmission electron microscopy image of the Mo2C-PtO material prepared in Example 2 of the present invention;

[0033] Fig. 9 This is a transmission electron microscope image of the Mo2C-PtO material prepared in Example 3 of the present invention;

[0034] Fig.10Polarization curves of the electrocatalytic hydrogen evolution reaction of the nano-molybdenum carbide materials prepared in Examples 1, 2, and 3 of the present invention in 1M KOH solution;

[0035] Fig.11 The Tafel slope diagram of the nano-molybdenum carbide material prepared in Examples 1, 2, and 3 of the present invention in 1M KOH solution;

[0036] Fig.12 This is a scanning electron microscope image of the material prepared in Comparative Example 1 of the present invention;

[0037] Fig.13 This is a transmission electron microscope image of the material prepared in Comparative Example 2 of the present invention;

[0038] Fig.14 XPS graphs of the materials prepared in Comparative Example 3 and Example 1 of the present invention;

[0039] Fig.15 Polarization curves of the electrocatalytic hydrogen evolution reaction of the nano-molybdenum carbide materials prepared in Example 1 and Comparative Examples 3 and 5 of the present invention in 1M KOH solution;

[0040] Fig.16 The Tafel slope graph of the nano-molybdenum carbide materials prepared in Example 1 and Comparative Examples 3 and 5 of the present invention in 1M KOH solution;

[0041] Fig.17 XPS graphs of the materials prepared in Comparative Example 4 and Example 1 of the present invention;

[0042] Fig.18 XPS graphs of the materials prepared in Comparative Example 5 and Example 1 of the present invention;

[0043] Fig.19 This is a transmission electron microscope image of the material prepared in Comparative Example 6 of the present invention;

[0044] Fig. 20 This is a transmission electron microscope image of the material prepared in Comparative Example 7 of the present invention. DETAILED DESCRIPTION

[0045] The principles and features of the present invention are described below in conjunction with examples, which are only used to explain the present invention and are not intended to limit the scope of the present invention. In addition, it is worth noting that the raw materials involved in the present invention are all common commercial products unless otherwise specified.

[0046] In the following examples, the nano Mo2C used is Mo2C nanosheets, and the specific preparation method includes the following steps: 0.5g of molybdenum disulfide, 1.6g of sodium carbonate and 5g of urea are ground and mixed evenly, and the temperature is raised to 850°C at a heating rate of 5°C / min in a tube furnace, and the temperature is kept for 4h, and the Mo2C nanosheets are obtained by cooling, washing and drying;

[0047] Example 1

[0048] A Mo2C-PtO catalyst, the preparation process diagram of which is shown in Figure 1 , specifically including the following steps:

[0049] 1) Take 500 mg Mo2C and add it into 64 mL of 0.2 mM / L chloroplatinic acid aqueous solution, that is, the mass ratio of Pt element to Mo2C is 1:100, and mix it by ultrasonic for 1 h to disperse it evenly.

[0050] 2) The mixed solution was placed in a magnetic stirring water bath, heated and stirred, and oxygen was continuously introduced at a flow rate of 160 sccm. The mixture was kept at 90° C. for 1 h and then cooled to room temperature.

[0051] 3) Wash with deionized water, filter and dry to obtain the Mo2C-PtO composite catalyst.

[0052] The XRD pattern of the product obtained in this example is shown in Figure 2 The obtained product is highly consistent with the characteristic peaks of the standard card Mo2C JCPDS#72-1683, but no PtO characteristic peaks are observed. Since the Pt loading is less than 5wt%, the characteristic peaks are masked by background noise.

[0053] Figure 4 This is a scanning electron microscope image of the product obtained in this example. The results show that the morphology of the obtained flaky Mo2C is well maintained. Figure 5 is a transmission electron microscope image of the product obtained in this example. After measurement, Figure 5 a shows the (101) crystal plane of PtO, whose interplanar spacing is 0.227 nm. Figure 5 The particle size of PtO nanoclusters on the Mo2C nanosheet support in a is about 2 nm. Figure 6 The elemental distribution map of the obtained product shows that fine PtO nanoclusters are uniformly dotted on the surface of the Mo2C nanosheet support.

[0054] 5 mg of the product obtained in this example was weighed and dispersed in 1 mL of isopropanol, and 20 μL of Nafion solution was dropped into it. After ultrasonication for 30 min, it was dropped onto a foam copper and dried to prepare a hydrogen evolution electrode. The electrode was placed in 1 M KOH for testing. The measured polarization curve and Tafel slope diagram of the electrocatalytic hydrogen evolution reaction were as shown in the figure. Fig.10 and Fig.11The results show that when the current density is 10 mA cm -2 When the overpotential of hydrogen evolution reaction is only 10mV, the Tafel slope is only 24mV dec. -1 , and at 1000mA cm -2 Under high current conditions, the overpotential is as low as 336 mV, showing excellent electrocatalytic hydrogen evolution performance.

[0055] Example 2

[0056] A Mo2C-PtO catalyst, the preparation method of which is substantially the same as that of Example 1, except that the volume of the chloroplatinic acid solution added in Example 1 is changed to 320 mL, the concentration is 0.4 mM / L, and the mass ratio of the Pt element to the Mo2C is 10:100.

[0057] Figure 2 The XRD spectrum shows that the product obtained in this example is Mo2C. Figure 7 The scanning electron microscope image in the figure shows that the product maintains the original Mo2C flake morphology. Figure 8 In the TEM image, it can be observed that the PtO particles are clearly distributed on the surface of the Mo2C support, and the particle size of the nanoclusters is about 5nm. This shows that with the increase of PtO loading, the particle size of the PtO nanoclusters grows.

[0058] Referring to the method described in Example 1, the polarization curve of the electrolysis of water and hydrogen evolution reaction and the Tafel slope diagram of the product obtained in this example are respectively as follows: Fig.10 and Fig.11 The results show that when the current density is 10 mA cm -2 When the overpotential of hydrogen evolution reaction is only 41mV, the Tafel slope is only 38mV dec. -1 And at 1000mA cm -2 Under high current conditions, the overpotential is as low as 475mV.

[0059] Example 3

[0060] A Mo2C-PtO catalyst, the preparation method of which is substantially the same as that of Example 1, except that the water bath temperature in Example 1 is changed to 50°C and the insulation time is 5h.

[0061] Figure 2 The XRD spectrum shows that the product obtained in this example is Mo2C. Fig. 9 It can also be clearly observed in the transmission electron microscopy image that there are uniformly dispersed PtO nanocluster particles on the Mo2C nanosheet matrix.

[0062] Referring to the method described in Example 1, the polarization curve of the electrolysis of water and hydrogen evolution reaction and the Tafel slope diagram of the product obtained in this example are respectively as follows: Fig.10 and Fig.11 The results show that when the current density is 10 mA cm -2 When the overpotential of hydrogen evolution reaction is only 63mV, the Tafel slope is only 52mV dec. -1 And at 1000mA cm -2 Under high current conditions, the overpotential is as low as 521mV.

[0063] Example 4

[0064] A Mo2C-PtO catalyst, the preparation method of which is substantially the same as that of Example 1, except that the gas flow rate in Example 1 is changed to 140 sccm.

[0065] Figure 3 The XPS spectrum in the figure shows that the Pt element in the product obtained in this example exists in the form of PtO, and the obtained PtO is relatively pure.

[0066] Example 5

[0067] A Mo2C-PtO catalyst, the preparation method of which is substantially the same as that of Example 1, except that the gas flow rate in Example 1 is changed to 200 sccm.

[0068] Figure 3 The XPS spectrum in the figure shows that the Pt element in the product obtained in this example exists in the form of PtO, and the obtained PtO is relatively pure.

[0069] Comparative Example 1

[0070] A Mo2C-PtO material, the preparation method of which is substantially the same as that of Example 1, except that the stirring temperature in the water bath is controlled to be 100° C. and the stirring time is controlled to be 2 h.

[0071] The SEM image of the product obtained in this comparative example is shown in Fig.12 ,The results show that if the water bath stirring temperature is too high, it will cause a certain degree of damage to the morphology of the Mo2C carrier.

[0072] Comparative Example 2

[0073] A Mo2C-PtO material, the preparation method of which is substantially the same as that of Example 1, except that the stirring temperature of the water bath is controlled to be 30°C.

[0074] The TEM image of the product obtained in this comparative example is shown in Fig.13 There is no PtO nanoclusters loaded on the surface of the Mo2C matrix. The results show that the temperature of the water bath stirring is too low to promote the decomposition and deposition of chloroplatinic acid on Mo2C.

[0075] Comparative Example 3

[0076] A Mo2C-PtO material, the preparation method of which is substantially the same as that of Example 1, except that the oxygen flow rate introduced during the reaction is controlled to be 300 sccm.

[0077] The XPS diagram of the product obtained in this comparative example is shown in Fig.14 The Pt element in the obtained product appears in a higher valence state of PtO2 close to 50%, and the obtained electrochemical activity diagram is shown in Fig.15 , Fig.16 The results show that if the continuous flow rate of the atmosphere is too fast, the Pt element will be over-oxidized, resulting in the formation of PtO2, and the electrochemical activity will be reduced accordingly.

[0078] Comparative Example 4

[0079] A Mo2C-PtO material, the preparation method of which is substantially the same as that of Example 1, except that the oxygen flow rate introduced during the reaction is controlled to be 220 sccm.

[0080] The XPS diagram of the product obtained in this comparative example is shown in Fig.17 The Pt element in the product exists in the form of a small amount of high-valent PtO2 and a majority of intermediate-valent PtO. The results show that when the oxygen flow rate exceeds 200 sccm, the amount of PtO2 generated will increase as the oxygen flow rate increases.

[0081] Comparative Example 5

[0082] A Mo2C-PtO material, the preparation method of which is substantially the same as that of Example 1, except that the oxygen flow rate introduced during the reaction is controlled to be 100 sccm.

[0083] The XPS diagram of the product obtained in this comparative example is shown in Fig.18 The obtained product contains low-valent Pt element and intermediate-valent PtO. The electrochemical activity diagram is shown in Fig.15 , Fig.16 The results show that the presence of Pt alone will reduce the electrochemical activity.

[0084] Comparative Example 6

[0085] A Mo2C-PtO material, the preparation method of which is substantially the same as that of Example 1, except that Mo2C is replaced by MoS2.

[0086] The TEM image of the product obtained in this comparative example is shown in Fig.19 In the obtained product, the Pt element formed relatively dense nanoparticles, resulting in agglomeration. The results showed that the bulk MoS2 could not provide enough attachment sites for Pt.

[0087] Comparative Example 7

[0088] A Mo2C-PtO material, the preparation method of which is substantially the same as that of Example 1, except that Mo2C is replaced by a carbon carrier.

[0089] The TEM image of the product obtained in this comparative example is shown in Fig. 20 In the obtained product, the Pt element agglomerated into relatively dense nanoparticles. The results show that it is difficult to highly disperse Pt on carbon materials using this synthesis method.

[0090] It should be noted that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, and these modifications and improvements all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A catalyst, characterized in that The catalyst comprises a nanostructured Mo2C carrier and PtO nanoclusters supported on the Mo2C carrier.

2. The catalyst according to claim 1, characterized in that The size of the PtO nanoclusters is 2-5 nm.

3. The catalyst according to claim 1, characterized in that The Pt loading is 0.1-10 wt %.

4. The catalyst according to claim 1, characterized in that The nanostructure morphology of the Mo2C is flake-shaped, flower-shaped, belt-shaped, tubular or linear.

5. The method for preparing the catalyst according to claim 1, characterized in that: The steps include: The nanostructured Mo2C support is mixed with a platinum-containing metal compound solution to obtain a mixed solution; The mixed solution was stirred and reacted at 50°C-95°C for 0.5h-5h, and the reaction atmosphere was continuously introduced; After the reaction is completed, the catalyst is obtained after filtering, washing and drying.

6. The preparation method according to claim 1, characterized in that: The concentration of the platinum metal compound solution is 0.2-0.4 mM / L.

7. The preparation method according to claim 1, characterized in that: The mass ratio of the Pt element content to Mo2C in the mixed solution is 1-10:

100.

8. The preparation method according to claim 1, characterized in that: The reaction atmosphere is oxygen or an atmosphere containing oxygen.

9. The preparation method according to claim 1, characterized in that: The flow rate of the reaction atmosphere is 140-200 sccm.

10. Use of the catalyst as claimed in claim 1 in electrocatalytic hydrogen production.

Citation Information

Patent Citations

  • Pt atomic cluster loaded WO3 nanosheet hydrogen evolution reaction catalyst and preparation method thereof

    CN111298790A